A cm-scale, low wind velocity and 250°C-compliant airflow-driven harvester for aeronautic applications. (November 2019) - Gasnier, P; Willemin, J; Boisseau, S; Goubault De Brugière, B; Pillonnet, G; Gomez, B; Neyret, I
Abstract: This paper reports the design, fabrication, and testing of a centimeter-scale (Ørotor =35mm), 250°C-compliant microturbine for aeronautic applications. Dedicated to low-speed air flows (≈3 m/s and down to 2 m/s), this device is the first flow-driven harvester withstanding such high temperatures and high vibration levels (10 7 cycles at 20G). Furthermore, the proposed harvester exhibits the highest output power per unit cross sectional area compared to prior art in the cm-scale and low velocity ranges.